The Role of Free Tissue Transfer in Merkel Cell Carcinoma of the Head and Neck - Aldo V. Londino III; Brett A. Miles (Journal of Skin Cancer)
Merkel cell carcinoma (MCC) is an uncommon neuroendocrine malignancy with a propensity for the head and neck. It typically presents asymptomatically in elderly Caucasians and is characterized by early local and regional spread. There is currently limited data on the appropriate algorithm for treatment of MCC. However, multimodal therapy with wide surgical excision with or without radiation therapy has become standard of care. The location of the primary tumor and intensive adjuvant therapy is often required, provides a challenge to the reconstructive head and neck surgeon. Occasionally, free tissue transfer reconstructive techniques are employed in the reconstruction of MCC defects. This paper will discuss the role of free tissue transfer as a reconstructive option after surgery for advanced head and neck MCC.